Efektivitas Modul “Teknik Membatik Dengan Canting Tulis” Terhadap Hasil Belajar Siswa Mata Pelajaran Keterampilan - Lidia Yulianti Saphira; Jenny Sista Siregar; Sri Irtawidjajanti (CV. ULIL ALBAB CORP, 2025)
The research is motivated by low achievement in class 7th Grade students of Open Secondary School Cakung 1 in Skills subjects, especially using decorative motifs to textile materials. The previous learning condition was still dominated by conventional practices that led to inactive student participation. The purposes of this study were to determine how effective the Batik Technique module with Canting Tulis following the Discovery Learning method was in increasing students' learning outcomes. The study was a Classroom Action Research (CAR) employing the Kemmis & McTaggart model with four phases, i.e., planning, implementation, observation, and reflection, conducted in two cycles. The population of this study was 33 students. Data collection methods are observation, tests, interviews, and documentation, while the data analysis is conducted descriptively qualitatively and quantitatively. Data validation was conducted through data triangulation and methodological triangulation. The results showed an increase in the students’ average scores from 67.57 in the pre-test with a classical completeness rate of 42%, to 80.90 (61%) in a posttest in the first cycle. Since the minimum mastery criteria had not been achieved in the first cycle, a second cycle was implemented, which resulted in a posttest score of 85.15 (82%). These outcomes indicate that the implementation of modules via the Discovery Learning approach is effective in improving student learning achievement. This study manifests the importance of contextual learning media innovation to improve the quality of learning, especially for open schools.